2012
DOI: 10.1111/j.1558-5646.2012.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination and Reduced Cohort Duration Can Drive Virulence Evolution: Marek’s Disease Virus and Industrialized Agriculture

Abstract: Marek's disease virus (MDV),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 59 publications
2
92
0
5
Order By: Relevance
“…Atkins et al. (2012), in a study of MDV evolution, found that fitness was maximized at intermediate virulence levels, also in accord with the standard virulence–transmission trade‐off (Atkins et al., 2012). We should note that alternative assumptions on life‐history traits could have been made.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Atkins et al. (2012), in a study of MDV evolution, found that fitness was maximized at intermediate virulence levels, also in accord with the standard virulence–transmission trade‐off (Atkins et al., 2012). We should note that alternative assumptions on life‐history traits could have been made.…”
Section: Discussionmentioning
confidence: 61%
“…We found that increasing the cohort duration can select for lower virulence strains of MDV, a result also found by Atkins et al. (2012), and supported by the historical trend towards greater virulence as cohort durations have shortened (Atkins et al., 2012). As the cohort duration increases, the lifespan of the chicken increases, and so too does the lifespan of the parasites exploiting the host.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Unfortunately, MD vaccines are incapable of inducing a sterile immunity and allow the virulent virus strains to replicate and be transmitted into the environment through the vaccinated host (Zhang et al 2015). It is believed, that keeping host alive, vaccination prolongs the infection time of virulent strains and may cause evolution of MDV with increased virulence (Witter 1997, Atkins et al 2013, Hunt and Dunn 2013. This is why more virulent MDV pathotypes emerge, reducing the effectiveness of existing vaccines (Davison and Nair 2005, Hunt and Dunn 2015, Zhang et al 2015.…”
Section: Introductionmentioning
confidence: 99%